The Influence of Nanoparticle Shape on Protein Corona Formation. Issue 25 (14th May 2020) - Madathiparambil Visalakshan, Rahul; González García, Laura E.; Benzigar, Mercy R.; Ghazaryan, Arthur; Simon, Johanna; Mierczynska‐Vasilev, Agnieszka; Michl, Thomas D.; Vinu, Ajayan; Mailänder, Volker; Morsbach, Svenja; Landfester, Katharina; Vasilev, Krasimir
Abstract: Nanoparticles have become an important utility in many areas of medical treatment such as targeted drug and treatment delivery as well as imaging and diagnostics. These advances require a complete understanding of nanoparticles' fate once placed in the body. Upon exposure to blood, proteins adsorb onto the nanoparticles surface and form a protein corona, which determines the particles' biological fate. This study reports on the protein corona formation from blood serum and plasma on spherical and rod‐shaped nanoparticles. These two types of mesoporous silica nanoparticles have identical chemistry, porosity, surface potential, and size in the y ‐dimension, one being a sphere and the other a rod shape. The results show a significantly larger amount of protein attaching from both plasma and serum on the rod‐like particles compared to the spheres. Interrogation of the protein corona by liquid chromatography–mass spectrometry reveals shape‐dependent differences in the adsorption of immunoglobulins and albumin proteins from both plasma and serum. This study points to the need for taking nanoparticle shape into consideration because it can have a significant impact on the fate and therapeutic potential of nanoparticles when placed in the body. Abstract : The role of nanoparticle shape in protein corona formation from human serum and plasma is studied using spherical and rod‐shaped mesoporous nanoparticles. Nanoparticles with identical surface chemistry but different shapes result in different protein corona compositions in serum and plasma. Rod‐shaped particles adsorb more immunoglobulins compared to the spherical particles.